DOI: 10.11606/d.25.2021.tde-18112021-161949
|View full text |Cite
|
Sign up to set email alerts
|

New design of titanium plate for minimally invasive treatment of mandibular fractures

Abstract: Novo modelo de placa de titânio para tratamento minimamente invasivo de fraturas mandibularesMuitas modalidades de tratamento e várias técnicas de fixação para fraturas maxilofaciais foram sugeridas na literatura. Alguns autores sugeriram novos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…2,7,13 Various alloplastic materials have been applied for OAC closures. Goldman et al 14 and Salman and Salman 15 reported a gold foil and gold plate for the closure of OAC. The gold foil is placed on the defect with the extension on healthy bone.…”
Section: Discussionmentioning
confidence: 99%
“…2,7,13 Various alloplastic materials have been applied for OAC closures. Goldman et al 14 and Salman and Salman 15 reported a gold foil and gold plate for the closure of OAC. The gold foil is placed on the defect with the extension on healthy bone.…”
Section: Discussionmentioning
confidence: 99%